STUDENTS’ BELIEFS ON CORRECTIVE FEEDBACK IN LANGUAGE LEARNING: BASIS FOR DEVELOPING HIGH SCHOOL STUDENTS’ TYPOLOGY - MARVIN JOHN C. CORPUZ (SEAQIL Journal of Language Education, 2023)
Corrective feedback has been one disputable concept in language learning for experts argued regarding its effectiveness and possible harmful side-effects. Hence, this study aimed to describe the beliefs systems of students regarding corrective feedback in language learning in terms of self-efficacy, effort, language anxiety, and learning strategy. Participants were 100 grade ten students of Gen. Tiburcio de Leon National High School who answered the validated researcher-made survey questionnaire. The results revealed that students agreed on the efficiency of corrective feedback in language learning which indicates that students have underlying positive beliefs regarding corrective feedback. Data were also analyzed to identify the significant relationship between the beliefs on Oral corrective feedback (OCF) and written corrective feedback (WCF) and their relationship to students’ academic performance using Statistical Package for Social Sciences (SPSS). Findings showed that there was a moderate correlation between the students’ beliefs on OCF and WCF. Furthermore, students’ academic performance has a weak correlation with WCF in terms of self-efficacy and has no correlation to other key concepts of beliefs system. These findings became the bases on developing Filipino High School students’ typology on corrective feedback explaining that students had unknowingly held layers of beliefs on corrective feedback which described as frontline belief system and embedded beliefs system. The study recommends that the output must be used as guide or aid to ESL teachers and instructors in delivering student-friendly language learning experience as part of students’ holistic development.